Filling Mixtures and Legislative Aspects of Their Application for the Disposal of Mine Workings - Orlíková, Alena (GeoScience Engineering, 2013)
The paper deals with the legislative aspects of the use of filling mixtures during the remediation of mining activities. The enterprises, carrying out the disposal of mine workings, buy filling mixtures within public procurement and need the quality of the products to be guaranteed. The requirements laid down in the technical guidelines for the certification of specified construction products raise doubts about the safety of products in terms of hygiene, protection of health and the environment. Currently, legislative development is underway in this area, striving for the implementation of the REACH Regulation into technical guidelines and thus to achieve the filling mixture to be produced and used in a safe manner.